The Study of Mental Health and its Relationship with Quality of Life in Substance Dependents - Marzeh Efati; Mousa KafiMasole; Robabeh Delazar (Drug Control Headquarters, Research and Education Office, 2012)
Introduction: Substance dependents encounter with many problems which cause confusion in their quality of life. Method: This survey is a descriptive-analytical study. In this survey 150 persons of substance dependents who refer to addiction recovery centers at Rasht were selected by available sampling method. Information was collected via mental health questionnaire (GHQ-28) and quality of life questionnaire of World Health Organization. Results: Findings showed a significant relation between quality of life and mental health of substance dependents. Also results of simultaneous regression showed that many components of quality of life were correlated to mental health components. Mental health domain of quality of life showed significant correlation with 3 domains namely: anxiety, social dysfunction and depression. Also physical health domain of quality of life showed significant correlation with somatization domain of mental health. Conclusion: It could be possible to increase mental health of substance dependents by improving of quality of life, in accordance to survey findings.